Cryptocurrencies in A Global Islam Economy (Study Mini Review) - Ni Nyoman Sawitri (Journal of Accounting and Finance Management, 2021)
The development of the digital era is increasingly widespread, encouraging changes in the payment system that provides services that facilitate economic activity. This also affects the economic behavior of the community. For example, the emergence of crypto currency or cryptocurrency as a digital currency, has almost the same function as other currencies. The difference is, crypto currencies do not have a physical form like fiat currency but in the form of blocks of data bound by hashes as validation. Despite providing a number of advantages for its users, the existence of cryptocurrency in Indonesia is still subject to debate both in terms of regulation and legality, especially from the perspective of Islamic sharia for its use. This article is conducted to review cryptocurrencies that are widely used in transactions, especially investments from the perspective of Islamic law. This research is a qualitative literature review. The data analysis technique in this study is descriptive-analytical with a normative juridical approach to Islamic law. Based on a number of references cited in this study, it is known that investing with cryptocurrency has a very high risk because its value can rise or fall derastically and predictably.